2013
DOI: 10.1094/pdis-03-12-0260-re
|View full text |Cite
|
Sign up to set email alerts
|

Spore Trapping and Pathogenicity of Fungi in the Botryosphaeriaceae and Diaporthaceae Associated with Avocado Branch Canker in California

Abstract: Avocado branch canker in California is caused by a complex of fungal species in the families Botryosphaeriaceae and Diaporthaceae. As the popularity of avocado fruit increases, California growers are under pressure to increase their productivity in order to compete with imports. One way to increase production is through high-density planting, which entails intense canopy management, possibly leaving the trees vulnerable to infection through pruning wounds. A spore trap study was undertaken to determine the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
2
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
8
2
1
Order By: Relevance
“…were not always correlated with rainfall. Similar results were found with other spore trap studies in California (Eskalen and Gubler 2001;Eskalen et al 2013;Úrbez-Torres et al 2010). Wounding is also known to predispose plants to infection by Colletotrichum (Lubbe et al 2006;Muimba-Kankolongo and Bergstrom 1992;Shaw 1995) and typical agricultural practices and the environment in CA citrus groves (pruning, shearing, wind/sand damage) give both of these species the opportunity to colonize citrus trees.…”
Section: Discussionsupporting
confidence: 91%
“…were not always correlated with rainfall. Similar results were found with other spore trap studies in California (Eskalen and Gubler 2001;Eskalen et al 2013;Úrbez-Torres et al 2010). Wounding is also known to predispose plants to infection by Colletotrichum (Lubbe et al 2006;Muimba-Kankolongo and Bergstrom 1992;Shaw 1995) and typical agricultural practices and the environment in CA citrus groves (pruning, shearing, wind/sand damage) give both of these species the opportunity to colonize citrus trees.…”
Section: Discussionsupporting
confidence: 91%
“…In California, New Zealand and South Africa the imperfect stage, Phomopsis spp. have been reported as pathogens of minor importance on avocado in both pre-and postharvest situations (Hartill and Everett 2002;Eskalen et al 2013;Twizeyimana et al 2013). Considering that several Diaporthe spp.…”
Section: Discussionmentioning
confidence: 99%
“…Peronospora effusa was detectable at all sites more or less continuously throughout both growing seasons in 2013 and 2014. In comparable studies of other plant pathogens, detection of airborne inoculum has been found to be more sporadic (Carisse et al 2009;Eskalen et al 2013;Granke et al 2009). Overlapping crops of spinach are planted in the Salinas Valley from February through November, and new production practices, such as wider planting beds, ensure dense plantings.…”
Section: Discussionmentioning
confidence: 99%
“…Overlapping crops of spinach are planted in the Salinas Valley from February through November, and new production practices, such as wider planting beds, ensure dense plantings. Overhead irrigation is a routine practice, providing ample moisture for the sporulation and splash dispersal of many fungal and oomycete pathogens (Eskalen et al 2013;Savory et al 2011;Úrbez-Torres et al 2010). Moreover, the northern end of the valley is regularly inundated with a marine fog layer.…”
Section: Discussionmentioning
confidence: 99%